Liquid crystal templating of mesoporous materials - Seddon,JM; Raimondi,ME (Molecular Crystals and Liquid Crystals Science and Technology Section A Molecular Crystals and Liquid Crystals, 2000)
There is currently great interest in the use of lyotropic liquid crystals as templates for the production of mesoporous inorganic or metallic materials having uniform pore sizes in the range 20-100 A or greater. Such materials have potential applications as catalysts, molecular sieves or electrodes, and can accommodate molecules which are too large to fit within the pores of conventional zeolites. We have investigated the structure and alignment of mesoporous materials produced using the True Liquid Crystal Templating (TLCT) method. In TLCT, the surfactant forms a lyotropic liquid crystal phase of well defined geometry and dimensions at the start of the synthesis. We have been able to produce hexagonal mesoporous coatings within capillaries, having a specific alignment of the 2-D hexagonal lattice, as probed by X-ray diffraction. We have also followed the structural kinetics of the alignment process. These TLCT mesoporous materials may be functionalized for catalytic applications. © 2000 OPA (Overseas Publishers Association) N.V. Published by license under the Gordon and Breach Science Publishers imprint.